1996
DOI: 10.2737/pnw-rp-497
|View full text |Cite
|
Sign up to set email alerts
|

Tailed frogs: distribution, ecology, and association with timber harvest in northeastern Oregon.

Abstract: SummaryBull, Evelyn L.; Carter, Bernie E. 1996. Tailed frogs: distribution, ecology, and association with timber harvest in northeastern Oregon. Res. Pap. PNW-RP-497. Portland, OR: U.S. Department of Agriculture, Forest Service, Pacific Northwest Research Station. 11 p.Tailed frogs (Ascaphus truer) were found in 42 of 80 streams surveyed in Union, Umatilla, Wallowa, and Baker Counties in 1992. At least three size classes of larvae were identified in seven of the streams, thereby suggesting that larvae transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Some studies reported little to no effect (West et al, 1980;Bull and Carter, 1996;Messere and Ducey, 1998;Gitzen and West, 2002;Hicks and Pearson, 2003;Frederickson and Frederickson, 2004;Fuller et al, 2004), others negative effects (Duguay and Wood, Wolff and Zasada, 1975;Waters and Zabel, 1995;Naughton et al, 2000;Morneault et al, 2004), and others still, positive effects (Von Treba et al, 1998;Ross et al, 2000;Fuller et al, 2004). These mixed findings are due to several factors.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Some studies reported little to no effect (West et al, 1980;Bull and Carter, 1996;Messere and Ducey, 1998;Gitzen and West, 2002;Hicks and Pearson, 2003;Frederickson and Frederickson, 2004;Fuller et al, 2004), others negative effects (Duguay and Wood, Wolff and Zasada, 1975;Waters and Zabel, 1995;Naughton et al, 2000;Morneault et al, 2004), and others still, positive effects (Von Treba et al, 1998;Ross et al, 2000;Fuller et al, 2004). These mixed findings are due to several factors.…”
Section: Introductionmentioning
confidence: 79%
“…In a literature review, deMaynadier and Hunter (1995) identified only one study of the effects of uneven-aged harvests on amphibians. I found nine published studies that sampled amphibians in selectively harvested stands or landscapes (Bull and Carter, 1996;Messere and Ducey, 1998;Naughton et al, 2000;Ross et al, 2000;Duguay and Wood, 2002;Hicks and Pearson, 2003;Frederickson and Frederickson, 2004;Morneault et al, 2004). In addition, I also found nine studies on small mammals in selectively harvested stands (Wolff and Zasada, 1975;West et al, 1980;Waters and Zabel, 1995;Von Treba et al, 1998;Carey, 2000;Sullivan and Sullivan, 2001;Gitzen and West, 2002;Klenner and Sullivan, 2003;Fuller et al, 2004).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Given the observed declines of southern populations following anthropogenic disturbances (Hawkins et al 1988;Bull and Carter 1996;Hawkes and Gregory 2012), there is concern that tailed frogs at the northern extent o f their distribution may also be negatively affected by activities such as forest harvesting, stream diversion, or the creation o f linear corridors. However, the possible impacts are speculative as our knowledge o f habitat requirements for the terrestrial life-stage of the species is limited.…”
Section: Previous Post-metamorphic Researchmentioning
confidence: 99%
“…Breeding occurs in early fall (September to October) depending on the geographic location (Green and Campbell 1984). The genus has evolved internal fertilization as a reproductive strategy because breeding occurs in flowing streams or small pools close to larval streams (Green and Campbell 1984;Bull and Carter 1996;Ritland et al 2000). Clutch sizes for A. truei range from 44-85 eggs deposited in double strands under rocks in cool-flowing streams ) from late June to early July following the fall breeding.…”
Section: Species Ecology and Biologymentioning
confidence: 99%